Mediating Effect of Career Decision Self-Efficacy on the Relation of Perfectionism to Career Indecision - Muliasari, Mona; Sugiyo, Sugiyo; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2020)
The purpose of this research was to identify and analyze the prediction effects of perfectionism on the career decision self-efficacy and career indecision, career decision self-efficacy on the career indecision and the mediating effect of career decision self-efficacy on the relationship between perfectionism and career indecision. The sample involved 369 high school students selected using random cluster sampling. The research method used is a structural equation model. The results showed that self-oriented perfectionism positively predicted career decision self-efficacy while socially prescribed perfectionism negatively predicted career decision self-efficacy, as well as career decision self-efficacy to predict career indecision. Also, career decision self-efficacy has a mediating effect on the relationship of perfectionism with career indecisions. The implications of the findings of this study are discussed in the article.